Prinsip Bisnis Qur’ani dalam Jual Beli: Tinjauan Tafsir al-Munir QS Al-Baqarah dan Al-Mutaffifin: Qur'anic Business Principles in Trade: A Study of al-Munir's Interpretation of Surah Al-Baqarah and Al-Mutaffifin - Maulana, Achmad Ilham; Safitri, Nurul Ani (Journal of Islamic Economics and Philanthropy, 2025)
This study aims to explore Qur'anic business principles in the context of trade, as reflected in Surah Al-Baqarah and Surah Al-Mutaffifin, using a thematic interpretation approach based on Tafsir al-Munir by Wahbah al-Zuhaili. The main focus is to identify ethical values in Islamic business derived from these two chapters, particularly regarding fairness in transactions and the prohibition of fraudulent practices. This research employs a qualitative method with thematic analysis of relevant verses and their interpretation. The findings reveal key principles emphasized in the Qur'an, including justice, the prohibition of usury and deceit, mutual consent in agreements, and ethical conduct in business such as honesty and trustworthiness. Surah Al-Baqarah highlights justice and the prohibition of riba in financial dealings, while Surah Al-Mutaffifin strongly condemns cheating in measurements and weights. These insights affirm the relevance of Qur'anic principles in shaping a just, transparent, and socially responsible business system.